Incidence and Risk Factors of Post Dural Puncture Headache After Spinal Anesthesia in Tripoli Hospitals - Abdurraouf Said; Hosam Elmahmoudi; Aisha Elansari; Lamia Elbadri; Shaima Elfakhri; Aya Alhejaji (AlQalam Journal of Medical and Applied Sciences, 2024)
Post Dural Puncture Headache (PDPH) remains a prominent clinical concern to the present day and common complication seen in the field of anesthesiology and pain medicine. Identification of such risk factors is a crucial step in the rational modification of anesthetic practice and evaluation of therapeutic interventions. This study was conducted to demonstrate the incidence and risk factors of PDPH in patients after spinal Anesthesia during three days’ post operations at general hospital in Tripoli, Libya. In this study certain factors related to patient history, baseline clinical state or anesthetic technique might be associated with an increased risk for this side effect, so it was collected historical, physiologic, and technical data to determine their association with PDPH. Out of total of 100 patients distributed over 5 different hospitals admitted over a period (from November 2020 to April 2021) 27% of them have a PDPH, while 92.5% of cases with PDPH are females, that 55.6% of PDPH cases are between 20 and 25 years old, and this percentage getting smaller as patients get older, most of the operations were caesarean section, at a rate of 58%, followed by lower abdominal surgeries with 19% of cases, and orthopedic surgeries with 17% of cases, while the lowest percentage was for the Urologic surgeries. 55% of cases with PDPH are classified as (case I), and 44% of them are classified as (case II), 81.5% of PDPH cases used noncutting needles. In this study the PDPH remains the most problem in hospitalized patients after spinal Anesthesia at Tripoli hospitals can be caused by variety of risk factors, associated with ASA physical states, nonprofessional technique, the females are more common than males and the percentage increasing in early age group. لا يزال صداع ما بعد ثقب الجافية مصدر قلق سريري بارز حتى يومنا هذا ومن المضاعفات الشائعة التي تظهر في مجال التخدير وطب الألم. يعد تحديد عوامل الخطر هذه خطوة حاسمة في التعديل العقلاني لممارسة التخدير وتقييم التدخلات العلاجية. أجريت هذه الدراسة لتوضيح مدى حدوث وعوامل خطر الإصابة بصداع ما بعد ثقب الجافية في المرضى بعد التخدير النخاعي خلال ثلاثة أيام بعد العمليات في المستشفى العام في طرابلس، ليبيا. في هذه الدراسة، قد ترتبط بعض العوامل المتعلقة بتاريخ المريض أو الحالة السريرية الأساسية أو تقنية التخدير بزيادة خطر هذا التأثير الجانبي، لذلك تم جمع البيانات التاريخية والفسيولوجية والتقنية لتحديد ارتباطها بصداع ما بعد ثقب الجافية. من بين إجمالي 100 مريض موزعين على 5 مستشفيات مختلفة تم قبولهم خلال فترة (من نوفمبر 2020 إلى أبريل 2021)، 27% منهم مصابون بصداع ما بعد ثقب الجافية ، في حين أن 92.5% من حالات صداع ما بعد ثقب الجافية هم من الإناث، وأن 55.6% من حالات صداع ما بعد ثقب الجافية تتراوح أعمارهم بين 20 عامًا. و25 سنة، وتقل هذه النسبة مع تقدم السن، وكانت معظم العمليات قيصرية بنسبة 58%، تليها جراحات أسفل البطن بنسبة 19% من الحالات، وجراحات العظام بنسبة 17% من الحالات، بينما كانت أقل نسبة لعمليات جراحة المسالك البولية. 55% من حالات صداع ما بعد ثقب الجافية تصنف على أنها (الحالة الأولى)، و44% منها تصنف على أنها (الحالة الثانية)، 81.5% من حالات صداع ما بعد ثقب الجافية تستخدم إبر غير قابلة للقطع. في هذه الدراسة، يظل صداع ما بعد ثقب الجافية هو المشكلة الأكثر لدى المرضى في المستشفى بعد التخدير النخاعي في مستشفيات طرابلس يمكن أن يكون ناجمًا عن مجموعة متنوعة من عوامل الخطر، المرتبطة بالحالات الفيزيائية ASA، والتقنيات غير المهنية، وتكون الإناث أكثر شيوعًا من الذكور وتزداد النسبة في سن مبكرة. مجموعة.